THERMAL STRUCTURE OF CONTINENTAL UPPER MANTLE INFERRED FROM S-WAVE VELOCITY AND SURFACE HEAT FLOW - Röhm A.H.E.; Snieder R.; Goes S.; Trampert J. (My University, 2000)
Results from seismic tomography provide information on the thermal structure of the continental upper mantle. This is borne out by the good agreement between tectonic age, surface heat flow and a tomographic S-wave velocity model for depths less than 180 km. The velocity anomalies of tomographic layers deeper than 230 km have relatively small amplitudes and show little correlation with surface heat flow or shallow velocities. We associate the drop in correlation and amplitude of the velocity perturbations between 180 and 230 km depth with the maximum thickness of the thermal boundary layer (TBL), in which larger variations in temperature and possibly composition than in the underlying convecting mantle can be sustained. Velocity profiles for different tectonic provinces are converted to temperature using mineralogical data. Both anharmonic and anelastic effects on the wave speeds are taken into account. The resulting geotherms differ most at depths of 60–120 km with variations of up to 900°C. Below 230 km, differences do not exceed 300°C. These geotherms agree well with one-dimensional conductive geotherms for the observed range of continental heat flow values using the empirical relationship that 40% of the surface heat flux stems from upper crustal radiogenic heat production. The S-wave velocity in the continental upper mantle appears to be adequately explained (within the uncertainties of the tomography and the conversion to temperature) by a thermal signature. A compositional component can, however, not be ruled out as it may have only a minor effect on the velocity and the heat flow. The surface heat flow is controlled by the shallow heat production and the thickness of the TBL. Seismology helps to determine the relative importance of the two factors and our results confirm the similar importance of both factors. Variations of TBL thickness could be controlled by compositional differences and/or by the effect of temperature on the rheology.